IN STUDENTS VOCAL CHOIR QUALIFICATIONS OF FORMATION NEW EDITORIAL TECHNOLOGY AND METHODS (Multidisciplinary Journal of Science and Technology, 2024)
Article in students  vocals - chorus qualifications to form dedicated. In it to sing of qualifications  theoretical basics with get to know  one in line education in the process general didactic  and special music of pedagogy main principles and their content - essence to students absorb